Clinical and Molecular Characteristics of SLC16A2 (MCT8) Mutations in Three Families with the Allan–Herndon–Dudley Syndrome. Issue 3 (5th January 2017) - Novara, Francesca; Groeneweg, Stefan; Freri, Elena; Estienne, Margherita; Reho, Paolo; Matricardi, Sara; Castellotti, Barbara; Visser, W. Edward; Zuffardi, Orsetta; Visser, Theo J.
Abstract : Mutations in the thyroid hormone transporter SLC16A2 (MCT8) result in the Allan‐Herndon‐Dudley syndrome (AHDS), characterized by severe intellectual disability and abnormal serum thyroid hormone levels. Here, we report 3 newly identified AHDS patients, of whom 2 carry a different mutation affecting the same Gly564 residue (p.G564E and p.G564R). Interestingly, a striking difference in severity of the clinical phenotype was observed between these 2 patients, which corresponded to the residual transporter activity of both mutant transporters in our in vitro studies. ABSTRACT: Mutations in the thyroid hormone transporter SLC16A2 (MCT8) cause the Allan–Herndon–Dudley Syndrome (AHDS), characterized by severe psychomotor retardation and peripheral thyrotoxicosis. Here, we report three newly identified AHDS patients. Previously documented mutations were identified in probands 1 (p.R271H) and 2 (p.G564R), resulting in a severe clinical phenotype. A novel mutation (p.G564E) was identified in proband 3, affecting the same Gly564 residue, but resulting in a relatively mild clinical phenotype. Functional analysis in transiently transfected COS‐1 and JEG‐3 cells showed a near‐complete inactivation of TH transport for p.G564R, whereas considerable cell‐type‐dependent residual transport activity was observed for p.G564E. Both mutants showed a strong decrease in protein expression levels, but differentially affected V max and K m values of T3 transport. Our findings illustrate that different mutations affecting the same residue may have a differential impact on SLC16A2 transporter function, which translates into differences in severity of the clinical phenotype.